PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI DAN PENGENDALIAN INTERN TERHADAP KETEPATANWAKTU PELAPORAN LAPORAN KEUANGAN DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Grobogan) - Nisaul Maulidah, 14.05.52.0124; Rizal, Alimuddin (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the influence of Human Resource Competence, Technology utilization and Internal Control to the timeliness of reporting of local financial statements. In this study researchers used a quantitative approach, using primary data through questionnaires. Respondents in this research are employees in the finance section of SKPD Kabupaten Grobogan (103 Responden). Variables in this research are human resource competence, technology utilization, and internal control as independent variable, and accuracy of reporting time of local financial report as dependent variable Data analysis used statistic method of multiple regression analysis. The result of hypothesis testing shows that the competence of human resources has no effect on the accuracy of reporting time of local financial report but the utilization of technology and internal control significant to the accuracy of reporting time of local financial report at SKPD Kabupaten Grobogan. Keywords: Timeliness of reporting of regional financial report, human resources competence, technology utilization, internal control.